Taxonomic revision of Paraphasma Redtenbacher, 1906 (Phasmatodea, Pseudophasmatidae) based on phallic and external morphology - Chiquetto-Machado, Pedro I.; Morales, Adriana C. [UNESP]; Cancello, Eliana M. (Magnolia Press, 2022)
Paraphasma Redtenbacher, 1906 is a genus of fully-winged stick insects occurring in central and northern South America. We carried out a morphology-based taxonomic revision of this genus with emphasis on the phallic organ, a structure that has been poorly explored for taxonomic purposes in Phasmatodea. Additionally, pairwise genetic distances between mitochondrial COI gene sequences were calculated for ten Paraphasma specimens representing six species. We recognize nine valid species in the genus plus one nomen dubium, Paraphasma fasciatum Gray, 1835. We redescribe Paraphasma and the species previously assigned to it, describe Paraphasma indistinctum Chiquetto-Machado sp. nov., Paraphasma sooretama Chiquetto-Machado sp. nov. and Paraphasma spinicauda Chiquetto-Machado sp. nov., and provide a key to the species in the genus. The male of Paraphasma minus Redtenbacher, 1906 is described for the first time, as well as the eggs of six species. We transfer Paraphasma amabile Redtenbacher, 1906 to Pseudophasma Kirby, 1896 (comb. nov.) and synonymize Pseudophasma xanthotaenidium Gnther, 1930 under this species (syn. nov.). In addition, Phasma perspicillaris Stoll, 1813 is removed from the synonymy of Paraphasma laterale (Fabricius, 1775) and synonymized under Parastratocles xanthomela (Olivier, 1792) (syn. nov.). The examination of the phallic organ was essential for species delimitation, as most species of Paraphasma are very similar in the external morphology of both sexes. The analysis of the COI sequences supported the species delimitation, resulting in remarkably lower pairwise distances between conspecific individuals (p-distance 2.0%) than between different species (p-distance 6.917.5%). We hope that this paper will stimulate further studies exploring the taxonomic and phylogenetic potential of the internal male genitalia of stick insects.